Engaged scholarship: developing management approaches in collaboration with industry - Mortara, Letizia (Henry Stewart Talks, 2024)
The engaged scholarship cycle, IfM (The Institute of Manufacturing), Design thinking, STIM (Strategic Technology and Innovation Management), Road-mapping